Penerapan Metode Teorema Bayes untuk Memprediksi Penyakit Tifus - Risdiana Risdiana; Hotler Manurung; Magdalena Simanjuntak (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
Typhoid is an acute febrile condition caused by infection with Salmonella enterica bacteria, especially the Salmonella typhi variant. Typhoid fever or what we usually know as typhoid fever. However, this disease can also be caused by other types such as Salmonella paratyphi A, Salmonella typhi B, and Salmonella paratyphi C. Typoid fever or typhus abdominalis is an acute infectious disease of the small intestine with symptoms of fever for one week or more accompanied by disorders of the intestinal tract. digestion and with or without impaired consciousness. Bayes' theorem is a theory of probability conditions that takes into account the possibility of an event (hypothesis) depending on other events (evidence). Future events can be predicted if previous events have occurred. Bayes' theorem is a mathematical equation used in probability and statistics to calculate conditional probabilities. In other words, it is used to calculate the probability of an event based on its relationship to other events. Based on the weight value given by the expert to each patient's typhoid symptom data, from the results of the analysis carried out with the diagnosis results from the consultation, the symptoms are High fever (lasting up to two weeks), Headache, Chills, Skin rash, Muscle and joint pain, Extreme fatigue, Dry cough, Confusion or delirium, Nausea and vomiting, Swollen spleen, Abdominal pain with predicted results for Epidemic Typhus with a value of 76.26%.